Hydronephrosis Resulting from Bilateral Ureteral Stenosis: A Late Complication of Polyoma BK Virus Cystitis?. (14th September 2010) - Basara, N.; Rasche, F.-M.; Schwalenberg, T.; Wickenhauser, C.; Maier, M.; Ivovic, J.; Niederwieser, D.; Lindner, T. H.
Abstract : We report here a case of acute lymphoblastic leukemia in remission presenting a late-onset bilateral hydronephrosis probably due to polyoma BK virus-induced proliferation of bladder endothelium on both ostii. The diagnosis was made virologically by BK virus Polymerase Chain Reaction (PCR) detection in the absence of any other bladder disease. Awareness of this late complication is necessary not only in patients after renal transplantation but also in patients after hematopoietic stem cell transplantation from matched unrelated donor.